The Canned Vegetables Research in the Forensic Commodity Examination - V. V. Egorova; I. L. Kazantseva (Теория и практика судебной экспертизы, 2020)
The course of a forensic analysis of long-term storage food products (canned vegetables) has been reviewed. The significance of the stage of external inspection, examination of the label is shown. The expertise objects are finished products of the canning industry in factory package (vegetable marinades and first courses). The objects were examined for compliance with the appropriate GOST requirements and technical specifications for organoleptic characteristics, net weight, mass fraction of ingredients.As a result of determining the organoleptic properties of canned vegetables “Pickled beetroot” the presence of individual pieces with black firm beet tissue has been detected which indicates violation of technological patterns of production. The presence of a particle of an outside impurity has also been detected that is a particle of paint coating based on alkyd binder and containing calcium carbonate as a filler which is unacceptable. The deviation of the canned vegetables net contents from the nominal amount indicated on the label meets the requirements of the regulations. For individual cans from the sample provided for analysis the experts have found non-compliance with the technical specifications for the rate “Mass fraction of vegetables from the total mass of canned goods”.When examining the canned good “First courses. Borsch with fresh cabbage” it has been identified that the samples have various labels on the consumer containers which indicates the presence of samples from different shipments.